Kerangka Regulasi dan Fatwa Transaksi Akad Hawalah Pada Perbankan Syariah - Nofrianto; Dhiyaa Meuthia Faiqah Erba; Riski Eka Lestari; Muhammad Raja Perkasa Alam Harahap (Al-Mizan (e-Journal), 2022)
Profit and loss is something that will be encountered in the business world. If there is a loss, one form of conception is the transfer of debt. This study aims to determine the application of the concept of debt transfer in Islam and its regulatory framework. The results of the study found that the transfer of a debt in Islam is known as hawalah. Hawalah is the transfer of debt or receivables from the creditor to the guarantor for repayment of the debt. The concept of hawalah is to transfer debt from muhil as the first debtor to the muhal'alaih as the second debtor. The application of hawalah in the world of Islamic banking consists of hawalah muqayaddah and hawalah mutlaqah. In addition, several regulations were found in the form of fatwas, but the rules of the hawalah’s fatwa still need to be studied further regarding their application in the service activities of Islamic finance companies.